PENGARUH EFIKASI DIRI TERHADAP MINAT BERWIRAUSAHA MAHASISWA DIPLOMA 3 TEKNIK SIPIL BANGUNAN GEDUNG FT UNP - Zul Fardi; Iskandar G. Rani (Universitas Negeri Padang, 2019)
Abstract— This study aims to reveal the effect of self-efficacy on the entrepreneurial interest of Diploma 3 Civil Engineering students in the UNP Building. This type of research is descriptive research. The population in this study were active students of Diploma 3 in Civil Engineering Building Class of 2016. The sample used in this study was total sampling, the entire population sampled as many as 42 students. Data were collected using a Likert scale questionnaire consisting of 5 answer choices. The number of statement items in the research questionnaire was 37 items. Based on simple regression analysis it can be seen the correlation / relationship value (R) of 0.395 and the coefficient of determination (R2) of 0.156 means that the effect of self-efficacy variables on the variable entrepreneurial interest is 15.6%, while the remaining 88.4% is influenced by variables other outside research. From the regression analysis it can also be seen that the t value is 2.718 greater than the t table value of 2.02108, then Ho is rejected and Ha is accepted, meaning that there is a significant influence between self-efficacy on entrepreneurial interests of Diploma 3 Civil Engineering students FT UNP Building. Keywords: Self-Efficacy, Entrepreneurial Interest.